Economic Factors and Conditions for the Transformation of the Education Services Market in the Context of Globalization - Nadtochy, Yulia V.; Klochko, Elena N.; Danilina, Marina V.; Gurieva, Lira K.; Bazhenov, Ruslan I.; Bakharev, Vladimir V. (International Review of Management and Marketing, 2016)
The globalization of the education market linkages identified organizations, education institutions, which revealed the need for significant changes in the system of HPE based on a partnership of government and business; the existing system of quality assurance of educational services of higher education, identified the optimal methodology for assessing the quality of the OS; the analysis of trends, effective models of system and process approaches in the framework of the organizational - economic mechanism to improve the quality of educational services. Verified educational services market requires a dynamic record of all development trends and changes taking place in all areas of functioning of the economic systems of individual countries. That allows you to respond promptly to request time to meet the requirements of the international community, and as a result - increase the capacity and create the necessary reserves to stabilize domestic socio-economic situation of the country. Keywords: economics, education, educational services, globalization JEL Classifications: A20; L11